Nucleotide sequence diversities of Chitinase and PR1 genes from Theobroma cacao cv. MCC 02 and Sulawesi 1 - AAN SETIOWATI; SINTHO WAHYUNING ARDIE; TRI JOKO SANTOSO; SUDARSONO SUDARSONO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Setiowati A, Ardie SW, Santoso TJ, Sudarsono. 2024. Nucleotide sequence diversities of Chitinase and PR1 genes from Theobroma cacao cv. MCC 02 and Sulawesi 1. Biodiversitas 25: 1-13. Cocoa (Theobroma cacao) faces vascular streak dieback (VSD) disease caused by Ceratobasidium theobromae, so disease control strategies are necessary, such as developing disease-resistant cocoa cultivars. Characterization of Chitinase (Chi) and Pathogenesis Related Protein 1 (PR1) could be the starting point for such purposes. This research aimed to characterize Chi-like and PR1-like genes from cocoa cv. MCC 02 (VSD resistant) and Sulawesi 1 (SUL 1, susceptible). The Chi-like and PR1-like amplicons were generated from cocoa cultivars, and sequencing of the amplicons generated 858 bp (Chi-like) and 569 bp (PR1-like). The multiple sequence alignment (MSA) of seven Chi-like fragments from two cocoa clones identifies four non-synonymous and two synonymous SNPs. The MSA of seven PR1-like fragments from two cocoa clones identifies three non-synonymous and two synonymous SNPs in the PR1-like coding and two SNPs in the 3’-non-coding regions. Phylogenetic tree construction among four TcChi-like accessions and 36 accessions from the NCBI Database indicates that all cocoa Chi-like genes are clustered in Clade II, separated from Chi-like of other species that belong to Clade I or Clade III. Phylogenetic tree construction among 24 accessions of PR1-like sequences from various plant species indicates that the cocoa PR1-like gene sequences are more closely related to Herrania umbratica and Theobroma grandiflorum.